J- and H-Aggregation of 5,10,15,20-Tetrakis-(4-sulfonatophenyl)porphyrin within Stimuli Responsive Complex Micelles via Electrostatic Interaction - Yu, Qingyuan; Wu, Chenglin; Wang, Fang (Asian Journal of Chemistry, 2014)
In aqueous solution, complex micelles were prepared by micellization of 5,10,15,20-tetrakis-(4-sulfonatophenyl)porphyrin (TPPS) and poly(2-(dimethylamino)ethyl methacrylate)-b-poly(N-isopropylacrylamide) (PDMAEMA-b-PNIPAM) at pH < 7 based on electrostatic interaction. The resultant complex micelles had a core-shell structure with complex TPPS/PDMAEMA as a core and PNIPAM as a shell. The anionic TPPS in the micellar core formed J-aggregates (pH 1.5) and H-aggregates (pH 3 - pH 7) due to electrostatic interaction with positive charged PDMAEMA. When the temperature was above the lower critical solution temperature (LCST) of PNIPAM, the thermo-responsive block collapsed on the complex micellar core, while the aggregation form of TPPS remained unchanged.